On the Path Loss Performance of Underwater Visible Light Communication Schemes Evaluated in Several Water Environments - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents an in-depth study into the necessity of efficient communication systems in underwater environments, with a primary focus on Underwater Visible Light Communication (UVLC). A novel path loss model that adapts to different water types is proposed to improve existing UVLC channel models. Validation against various scenarios, including different water types and receiver aperture diameters, is carried out using Monte Carlo simulations. The results demonstrate the efficiency and accuracy of the model by carefully fitting the actual performance of the UVLC systems. The results show a considerable improvement over previous models that only considered Lambert s path loss and geometric path loss. Despite some variations observed at larger distances between the transmitter and receiver, the proposed model exhibits significant promise in the understanding and application of UVLC in different underwater environments. This study serves as a preliminary step toward developing more sophisticated and efficient models for UVLC systems. © 2023 IEEE.